Causes of Prostate Cancer Recurrence After Radical Prostatectomy - Mukhtar, Denny (Riviera Publishing, 2025)
Prostate cancer recurrence following radical prostatectomy (RP) poses significant challenges for patient management and long-term outcomes. The objective of this study was to summarize the main factors associated with prostate cancer recurrence after radical prostatectomy. A scoping review was conducted using the PubMed database with keywords including ‘prostate cancer recurrence after radical prostatectomy,’ ‘biochemical recurrence,’ and ‘surgical margins.’ The search was limited to English-language studies published between 2020–2025. Inclusion criteria focused on clinical and case report studies involving recurrence post-RP with a minimum of 12-month follow-up. A total of 4,736 articles were identified, with 23 studies meeting all eligibility criteria. Recurrence was primarily associated with positive surgical margins, Gleason score, PSA kinetics, and molecular markers such as gene signatures and inflammation-related profiles. Salvage radiotherapy, especially when administered early, showed improved outcomes. Genetic and imaging advances contributed to improved risk stratification. The recurrence of prostate cancer after RP is influenced by surgical, biological, and individual patient factors. Early detection and risk-adapted interventions are crucial in improving survival and minimizing progression..